Water striders (Heteroptera: Gerromorpha: Gerridae) of Romania with an update on the distribution of Gerris gibbifer and G. maculatus in southeastern Europe - Berchi, Gavril Marius; Cianferoni, Fabio; Csabai, Zoltán; Damgaard, Jakob; Olosutean, Horea; Ilie, Daniela Minodora; Boda, Pál; Kment, Petr (Zootaxa, 2018)
The Romanian fauna comprises two species of Aquarius Schellenberg, 1800, eight species of Gerris Fabricius, 1794 and one species of Limnoporus Stål, 1868, and we hereby update the distribution and provide insights on the phenology and ecology of all eleven species in this country. We furthermore update the distribution of the two closely related species Gerris gibbifer Schummel, 1832 and G. maculatus Tamanini, 1946 in southeastern Europe. Gerris maculatus is recorded for the first time from Hungary, Montenegro and Slovenia, and the first detailed localities from Romania and Serbia are given. All bibliographic records of G. gibbifer from Romania, Macedonia and Serbia are based on misidentification and this species is thus excluded from the faunal lists of these countries. Both G. gibbifer and G. maculatus occur in Croatia, Hungary, Ukraine, and probably Slovenia.